Association between body weight variability and incidence of Parkinson disease: A nationwide, population‐based cohort study. (27th July 2021) - Park, Joo‐Hyun; Choi, Yeonjoo; Kim, Hyunjin; Nam, Myung Ji; Lee, Chung‐woo; Yoo, Ji Won; Jung, Jin‐Hyung; Park, Yong‐Gyu; Han, Kyungdo; Kim, Do‐Hoon
Abstract: Background and purpose: Although body weight variability has been associated with mortality, cardiovascular disease, and dementia, the relationship between body weight variability and Parkinson disease (PD) has rarely been studied. We aimed to investigate the longitudinal association between body weight variability and PD incidence. Methods: A nationwide population‐based, cohort study was conducted using the database from the Health Insurance Review and Assessment Service of the whole Korean population. We analyzed 2, 815, 135 participants (≥40 years old, mean age = 51.7 ± 8.6 years, 66.8% men) without a previous PD diagnosis. We determined individual body weight variability from baseline weight and follow‐up visits. We used Cox proportional hazards regression models. Results: The highest quartile group was associated with increased PD incidence compared with the lowest quartile group after adjustment for confounding factors (hazard ratio [HR] = 1.18, 95% confidence interval [CI] = 1.08–1.29). In contrast, baseline body mass index, baseline waist circumference, and waist circumference variability were not associated with increased PD incidence. In the body weight loss group, individuals within the quartile of the highest variation in body weight showed a higher HR of PD risk than those within other quartiles (HR = 1.41, 95% CI = 1.18–1.68). Conclusions: Body weight variability, especially weight loss, was associated with higher PD incidence. This finding has important implications for clinicians and supports the need for preventative measures and surveillance for PD in individuals with fluctuating body weight. Abstract : High variability of body weight was associated with an increased risk of Parkinson disease (PD) incidence, but baseline body weight was not associated with an increased risk of PD incidence. The association between body weight variability and PD risk did not differ according to age, sex, and comorbidities, including obesity. In the body weight loss group, individuals with high body weight variability had a further increased risk of PD.